Efficient Synthesis of 1-Amidoalkyl-2-Naphthols by One-Pot, Three-Component Reaction under Solvent-Free Conditions - Zahed Karimi-Jaberi; Marziyeh Jokar; S. Zoleykha Abbasi (Journal of Chemistry)
Two efficient and direct procedures have been developed for the preparation of 1-amidoalkyl-2-naphthols by a one-pot condensation of aldehydes, 2-naphthol, and amides in the presence of trichloroacetic acid or cobalt (II) chloride as catalyst. The reactions were carried out under solvent-free media. High yields, short reaction times, easy workup of the catalyst are advantages of these procedures.